Role of Digestive Tract Hormone in Functional Dyspepsia - Mohammad Adi Firmansyah; Dadang Makmun; Murdani Abdullah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Dyspepsia is a complaint commonly found in daily practice. Functional dyspepsia is considered if the organic cause of dyspepsia is not found. The pathophysiology of functional dyspepsia has not been fully understood.However there are three main pathophysiology, which are: motility disturbance, non-motility disturbance, and  psychosocial factor. Several digestive tract hormones are ghrelin, motilin, cholecystokinin (CCK), peptide YY (PYY), somatostatin, glucagon-like-peptide 1 (GLP), are thought to play role in the pathophysiology of functional dyspepsia, particularly in the regulation of digestive tract motility. Currently, a new paradigm in digestive tract disturbance treatment is developing, such as motilin receptor agonist therapy (for example mitemcinal) and ghrelin receptor agonist therapy, which is used as one of the new modalities in treatment of dyspepsia.Keywords: dyspepsia, functional dyspepsia, motilin, ghrelin, cholecystokinin, motilin receptor agonist, ghrelin receptor agonist